The Moderating Effect of Age on Low-Income Students' Relationships With Mentors and Their Self-Efficacy Since COVID-19 - Lee, Jaewon; Allen, Jennifer; Lim, Hyejung; Choi, Gyuhyun; Jung, Jiyu (Frontiers in Psychiatry, 2022)
Purposes This study investigates the moderating effect of age on the association between relationship with mentors and self-efficacy among low-income students. Methods A total of 255 low-income middle and high school students participated. The PROCESS macro 3.4 for Statistical Product and Service Solutions was employed to test the moderating effect. Results Quality of relationship between mentors and mentees was positively associated with mentees’ self-efficacy. Students’ age significantly moderated the association between quality of the relationship with mentors and self-efficacy. Discussion It is important to expand mentorship programs for low-income students during the COVID-19 pandemic in order to foster high self-efficacy among adolescents. Recruitment of high quality mentors and additional factors that may be helpful to a good relationship between mentees and mentors, such as mentor training, mentor screening, and mentor-mentee matching, should be prioritized to improve self-efficacy among low-income students since COVID-19. Early opportunities for mentoring from high quality mentors is particularly important to increase self-efficacy among younger students such as middle school students.